Small Primary Cutaneous γδT-Cell Lymphoma Lesions Successfully Treated With Pralatrexate. (February 2019) - Imataki, Osamu; Uchida, Shumpei; Yokokura, Shigeyuki; Uemura, Makiko; Kadowaki, Norimitsu
Abstract : Abstract: Here we report on the treatment of a 38-year-old woman with primary cutaneous γδT-cell lymphoma, which is a rare subset of cutaneous T-cell lymphoma. She presented with multiple subtle subcutaneous nodules, which were not clearly observed on computed tomography scans or after biopsy. However, 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG-PET) accurately detected small cutaneous lesions. She achieved a second complete remission, as demonstrated by 18 F-FDG-PET performed after pralatrexate infusion.